The Role of the Yerevan Faience Plant in Urban Lifestyle in the Middle of the XX Century - Avetisyan, Meri (History and Culture, 2026)
The integration of the Yerevan Faience Plant into Yerevan daily life is important for several reasons. Firstly, from the point of view of consumer services, the plant's products ensured the availability of necessary items for different social strata. However, it should be noted that thanks to its work, the plant went beyond the boundary of an entity of exclusively industrial importance and managed to take on other functions that were associated, in particular, with the formation of an urban lifestyle: for example, the plant managed to form a new level of taste and fashion in the society, formed a certain attitude towards utensils, taught people to bring beauty into everyday life.To the honor of the plant, it should be noted that the plant managed to solve the tasks assigned to it in the economic and socio-cultural sphere. Now, in connection with the new fashion standards and the variety of goods that the market offers, the plant's products are gradually being squeezed out of everyday life and transferred to museums. Despite this, the society continues to warmly treat the plant's products.
Keywords: industry; trademark; Armenian crystal; faience; traditions; urban life; utensils; Yerevan